APPLIED MODIFIED EXPONENTIAL APPROACH METHOD TO DETERMINE THE OPTIMAL SOLUTION - Pasaribu, Meliana; Helmi, Helmi; Pajriah, Dwi; Lestari, Devi Indah (PATTIMURA UNIVERSITY, 2025)
PT. IGM distributes vaccines to several cities within and outside West Kalimantan. Distribution can be carried out directly or through CV. XYZ. To maintain vaccine quality, an effective and efficient vaccine management plan is required, especially for storage and distribution, to prevent any deviations in these processes This is done to ensure the vaccine’s potency remains intact until it is ready for use. Distribution routes are chosen to be as efficient as possible. Therefore, this article discusses the application of the transportation method to manage vaccine distribution and minimize distribution costs. The distribution problem is formulated into a mathematical model and solved using the modified exponential approach method. This method is improvement on the improved Exponential Approach, focusing on the determination of initial solution and table revisions. Allocation is based on selecting cells with the smallest reduced cost entries. Based on research findings, PT IGM distributes vaccines to CV. XYZ, Pontianak and Kuburaya in amounts of 209.000 units, 151.000 units and 310.000 units, respectively. CV. XYZ distributes vaccines to Ketapang, Singkawang, Sintang and Bengkayang in amount of 40.000 units, 55.000 units, 45.000 units, and 9.000 units, respectively.